2012
DOI: 10.1128/aem.01126-12
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Genetic Introgression: High Levels of Intersubspecific Recombination Found in Xylella fastidiosa in Brazil

Abstract: b Documenting the role of novel mutation versus homologous recombination in bacterial evolution, and especially in the invasion of new hosts, is central to understanding the long-term dynamics of pathogenic bacteria. We used multilocus sequence typing (MLST) to study this issue in Xylella fastidiosa subsp. pauca from Brazil, a bacterium causing citrus variegated chlorosis (CVC) and coffee leaf scorch (CLS). All 55 citrus isolates typed (plus one coffee isolate) defined three similar sequence types (STs) domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(146 citation statements)
references
References 44 publications
9
135
2
Order By: Relevance
“…The availability of novel loci and alleles can result in the emergence of epidemic isolates that have the potential to exploit host plants previously not susceptible to disease as a result of X. fastidiosa infection. Although not conclusively demonstrated, independent studies have suggested that X. fastidiosa diseases can emerge via gene exchange between isolates (Almeida et al 2008;Nunes et al 2003;Nunney et al 2012). Therefore, increases in genetic diversity, driven by the introduction of foreign genotypes, carry risks that go beyond the potential host range of the newly arrived isolate.…”
Section: Quarantine Importancementioning
confidence: 99%
See 2 more Smart Citations
“…The availability of novel loci and alleles can result in the emergence of epidemic isolates that have the potential to exploit host plants previously not susceptible to disease as a result of X. fastidiosa infection. Although not conclusively demonstrated, independent studies have suggested that X. fastidiosa diseases can emerge via gene exchange between isolates (Almeida et al 2008;Nunes et al 2003;Nunney et al 2012). Therefore, increases in genetic diversity, driven by the introduction of foreign genotypes, carry risks that go beyond the potential host range of the newly arrived isolate.…”
Section: Quarantine Importancementioning
confidence: 99%
“…Both the coffee and citrus isolates of subspecies pauca appear to have acquired alleles from subspecies multiplex (Nunney et al 2012). Likewise, subspecies multiplex has participated in recombination with subspecies fastidiosa (Nunney et al 2010;Kung et al 2013).…”
Section: Comparative Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Because X. fastidiosa is naturally competent (Kung and Almeida 2011) and X. fastidiosa subsp. pauca infecting coffee and citrus has been suggested to be of recombinogenic origin (Nunney et al 2012), the departure from linkage equilibrium observed here may be a consequence of geographic structuring, admixture events, and limited genotype flow among the regions. In this case, linkage disequilibrium would occur due to barriers to gene exchange (e.g., geographic or ecological) or by an epidemic expansion in which case linkage disequilibrium would be temporary.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, it is plausible that the epidemiology of the diseases caused by X. fastidiosa subsp. pauca in citrus and coffee is similar, despite the fact that strains isolated from these host plants are distinct Nunney et al 2012).…”
mentioning
confidence: 94%